A study on environmental impact from construction operation in residential areas / Mohamad Khairul Nizam Abdul Ghani and Emma Marinie Ahmad Zawawi - Abdul Ghani, Mohamad Khairul Nizam; Ahmad Zawawi, Emma Marinie (2018)
Air pollution is a growing problem because of rising urban populations, new developments of housing, unchecked urban and industrial expansions and the phenomenal surge in the number and use of motor vehicles. Without a proper protection and mitigation plan, construction activities and new developments will cause uncomfortable conditions to nearby residential areas due to air pollution. This paper aims to highlight the impact of environment from construction operations based on experiences of the residents. The objectives are to identify the awareness of residents towards environmental impacts on their quality of life and to identify factors causing air pollution to the residential areas. Two locations in Shah Alam were chosen as a case study; Section U11 and Section U12. There are construction activities which operate at about 100-metre distance from the residential areas. A questionnaire survey was conducted in March 2018. 42 respondents were involved in this survey. The results revealed that many of the respondents were knowledgeable on the issues of environment but not many of them had taken a preventive measure to reduce this environmental impact. It is anticipated that this study will benefit both construction players and public to work together for a better quality of life though protecting our environment.